Catalytic oxidation of NO on activated carbons. (February 2019) - Fang, Zhongqiu; Yu, Xinhai; Tu, Shan-Tung
Abstract: The catalytic oxidation of NO using activated carbons provides a promising alternative for the control of emission of waste incineration plants air pollutant. In this study, an activated carbon named AC-1 was made from coconut shell and was activated using steam. It was found that the presence of oxygen promoted the NO removal significantly. The NO removal efficiency of AC-1 was approximately 87%. The investment cost for the case using AC-1 is 0.85 times that using selective catalytic reduction (SCR). In addition, the operation cost of the case using AC-1 was from 9.7% to 23.6% of that of SCR method. The potential of the AC-1 for the denitration of the waste incineration plants is promising.